Digital agriculture based on big data analytics: a focus on predictive irrigation for smart farming in Morocco - Loubna Rabhi; Noureddine Falih; Lekbir Afraites; Belaid Bouikhalene (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Due to the spead of objects connected to the internet and objects connected to each other, agriculture nowadays knows a huge volume of data exchanged called big data. Therefore, this paper discusses connected agriculture or agriculture 4.0 instead of a traditional one. As irrigation is one of the foremost challenges in agriculture, it is also moved from manual watering towards smart watering based on big data analytics where the farmer can water crops regularly and without wastage even remotely. The method used in this paper combines big data, remote sensing and data mining algorithms (neural network and support vector machine). In this paper, we are interfacing the databricks platform based on the apache Spark tool for using machine learning to predict the soil drought based on detecting the soil moisture and temperature.